Keterampilan Proses Sains dan Motivasi Belajar Sains pada Pembelajaran Kimia dengan LKPD STEM Melalui Formulasi Pembersih Lantai - Ridha Maulana; M. Adlim; Ibnu Khaldun (Postgraduate, University of Mataram, 2023)
This study aims to develop STEM student worksheets. The research method used is research and development (R&D) using the ADDIE model stages. Determination of the research sample using random sampling method with research subjects are students of class XI IPA 1 SMA Inshafuddin Banda Aceh. The results showed that students' science process skills increased significantly and were significantly different from the pretest based on the T-test. Students' science process skills increased in each indicator with an average N-gain score of 37 belonging to the medium category. Students' motivation to learn science is high with an average score of 87.38% belonging to the very good category.